2021
DOI: 10.1093/ijnp/pyab092
|View full text |Cite
|
Sign up to set email alerts
|

Towards Modeling Anhedonia and Its Treatment in Zebrafish

Abstract: Mood disorders, especially depression, are a major cause of human disability. The loss of pleasure (anhedonia) is a common, severely debilitating symptom of clinical depression. Experimental animal models are widely used to better understand depression pathogenesis, and to develop novel antidepressant therapies. In rodents, various experimental models of anhedonia have already been developed and validated. Complementing rodent studies, the zebrafish (Danio rerio) is emerging as a powerful model organism to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 206 publications
0
3
0
Order By: Relevance
“…Studies on zebrafish have identified modifications in neural circuits within these brain regions following exposure to stress or trauma [41]. Neurotransmitter systems have also been examined, with dysregulation of serotonin 5-hydroxytryptophan (5-HT) linked to anxietylike behavior in zebrafish subjected to stress paradigms [42]. Moreover, investigations into the HPA axis have revealed insights into dysregulation after stress exposure, leading to altered cortisol levels and stress-related behaviors [43,44].…”
Section: Neuroanatomical and Neurochemical Insights From Zebrafish Pt...mentioning
confidence: 99%
“…Studies on zebrafish have identified modifications in neural circuits within these brain regions following exposure to stress or trauma [41]. Neurotransmitter systems have also been examined, with dysregulation of serotonin 5-hydroxytryptophan (5-HT) linked to anxietylike behavior in zebrafish subjected to stress paradigms [42]. Moreover, investigations into the HPA axis have revealed insights into dysregulation after stress exposure, leading to altered cortisol levels and stress-related behaviors [43,44].…”
Section: Neuroanatomical and Neurochemical Insights From Zebrafish Pt...mentioning
confidence: 99%
“…In rats, chronic stress was found to decrease reward-seeking behaviours, exploration, and locomotor activity in rodents, and these reductions are regarded as loss of motivation. Anhedonia has been extensively studied in zebrafish with a recent review highlighting the behavioural tests used to study the various phenotypes of anhedonia ( de Abreu et al, 2022 ). Amongst them, the conditioned place preference (CPP) test could be implemented to mimic the effects of the sucrose preference test in rodents.…”
Section: Behavioural Tests In Fish Modelsmentioning
confidence: 99%
“…The animal model zebrafish has been gained ground in several fields of research and as a model for complex brain disorders [23]. It has also been used to evaluate the pathological mechanisms of affective disorders [24]. This can be achieved through the zebrafish's response to different stimuli, which allows researchers to study biological and pharmaceutical processes [25].…”
Section: Introductionmentioning
confidence: 99%